The policy of developing and managing library collections in libraries - Kadhim Hantoush, Ahmed; abdulhussein madhosh, Qader (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to show the importance of the policy of developing and managing library collections in libraries and information centers, regardless of the type of library. The factors that are taken into consideration during the process and development of the collection and it’s quality to serve the beneficiaries. These factors include the policies, principles, procedures, and problems associated with the community the library serves. Also, doing the collection evaluation process to find out the benefit of its use, in addition to developing the collections through electronic technologies. The research concluded that many libraries need to pay close attention to the growth and development of their library collections, which enhances the quality of the library and the quality of the services it provides to readers.